2021
DOI: 10.3352/jeehp.2021.18.12
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of clinical performance assessment of medical students on a virtual sub-internship in the United States

Abstract: We aimed to determine whether it was feasible to assess medical students as they completed a virtual sub-internship. Six students (out of 31 who completed an in-person sub-internship) participated in a 2-week virtual sub-internship, caring for patients remotely. Residents and attendings assessed those 6 students in 15 domains using the same assessment measures from the in-person sub-internship. Raters marked “unable to assess” in 75/390 responses (19%) for the virtual sub-internship versus 88/3,405 (2.6%) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Faculty and residents have responded favorably as well, finding virtual rotations useful for assessing student characteristics such as knowledge base and communication skills 14 . Common challenges reported by faculty included a limited ability to assess an applicant's fit for the program, lack of hands‐on experiences, and an increase in personal workload 16,18‐20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faculty and residents have responded favorably as well, finding virtual rotations useful for assessing student characteristics such as knowledge base and communication skills 14 . Common challenges reported by faculty included a limited ability to assess an applicant's fit for the program, lack of hands‐on experiences, and an increase in personal workload 16,18‐20 …”
Section: Discussionmentioning
confidence: 99%
“…14 Common challenges reported by faculty included a limited ability to assess an applicant's fit for the program, lack of hands-on experiences, and an increase in personal workload. 16,[18][19][20] In addition to facilitating connections between students and programs, virtual away rotations may also serve as an informal "signal" of an applicant's interest in a training program. In a recent analysis of otolaryngology preference signaling outcomes in the 2020 to 2021 and 2021 to 2022 application cycles, we found that on average 59.5% of preference signals resulted in an interview at that program.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, mentoring during e-internships leads to skills development and opportunities (Jeske & Linehan, 2020). In relation to the medical field, the study by Woller et al (2021) revealed that medical students were unable to assess the domains of physical examination, build rapport with patients, and show compassion during the virtual clerkship. It indicated that recording patients' information was harder to assess online.…”
Section: Contextmentioning
confidence: 99%